Strength in Numbers? The Power of Women in Icelandic Newsrooms - Nanna Árnadóttir 1985- (2010)
This dissertation is based on research conducted between January and April 2010 in Iceland. The purpose of the research was to examine the understanding of the distribution of influence between genders in Icelandic newsrooms as well as the perceptions of female news workers employed in the newsrooms of the following media outlets; RÚV, Morgunblaðið and Fréttablaðið. The research was both quantative, through the collection and dissemination of employment data at each newsroom, as well as qualitative, through the keeping of diaries as well as in-depth interviews conducted with nine participants. The employment information for each newsroom was split, where possible, into three categories: Journalist, Assistant Editor or Shift Editor and finally Editor. Following this the gender of each employee was recorded and thee data compared to conclude not only whether the gender ratios of the employees in each category were equal but also to assess overall the distribution of influence between the genders. Nine female participants were included in qualitative part of the research. Three from each news outlet. They were each asked to fill out a diary for two working days to reflect upon the role of gender in the newsroom and then asked to attend an in-depth interview to explore their perceptions of gender and power in their place of employment. The main results show that the most balanced newsroom in terms of gender ratios was RÚV and this notion was mirrored in the perceptions of participants employed there. The newsroom with the least balanced gender ratios was Morgunblaðið, these results were also mirrored in the perceptions of the participants employed there.